![\\z=3x+3y-x^2- xy-y^2+6\\ z'_x=3-2x-y\\ z'_y=3-x-2y\\\\ 3-2x-y=0\\ 3-x-2y=0\\\\ y=-2x+3\\ 3-x-2y=0\\\\ 3-x-2(-2x+3)=0\\ 3-x+4x-6=0\\ 3x=3\\ x=1\\\\ y=-2\cdot1+3\\ y=-2+3\\ y=1\\ \\z=3x+3y-x^2- xy-y^2+6\\ z'_x=3-2x-y\\ z'_y=3-x-2y\\\\ 3-2x-y=0\\ 3-x-2y=0\\\\ y=-2x+3\\ 3-x-2y=0\\\\ 3-x-2(-2x+3)=0\\ 3-x+4x-6=0\\ 3x=3\\ x=1\\\\ y=-2\cdot1+3\\ y=-2+3\\ y=1\\](https://tex.z-dn.net/?f=%5C%5Cz%3D3x%2B3y-x%5E2-+xy-y%5E2%2B6%5C%5C+z%27_x%3D3-2x-y%5C%5C+z%27_y%3D3-x-2y%5C%5C%5C%5C+3-2x-y%3D0%5C%5C+3-x-2y%3D0%5C%5C%5C%5C+y%3D-2x%2B3%5C%5C+3-x-2y%3D0%5C%5C%5C%5C+3-x-2%28-2x%2B3%29%3D0%5C%5C+3-x%2B4x-6%3D0%5C%5C+3x%3D3%5C%5C+x%3D1%5C%5C%5C%5C+y%3D-2%5Ccdot1%2B3%5C%5C+y%3D-2%2B3%5C%5C+y%3D1%5C%5C+)
(1,1)
0 \wedge z''_{xx}<0 \Rightarrow f(1,1)=f_{max}(x,y)\\\\ f_{max}(x,y)=3\cdot1+3\cdot1-1^2-1\cdot1-1^2+6\\ f_{max}(x,y)=3+3-1-1-1+6\\ f_{max}(x,y)=9 " alt="\\z''_{xx}=-2\\ z''_{yy}=-2\\ z''_{xy}=-1\\ \\\det\left[\begin{array}{cc}-2&-1\\-1&-2\end{array}\right]=(-2)^2-(-1)^2=4-1=3\\\\ \det>0 \wedge z''_{xx}<0 \Rightarrow f(1,1)=f_{max}(x,y)\\\\ f_{max}(x,y)=3\cdot1+3\cdot1-1^2-1\cdot1-1^2+6\\ f_{max}(x,y)=3+3-1-1-1+6\\ f_{max}(x,y)=9 " align="absmiddle" class="latex-formula">